ANALISIS KEPUASAN PENGUNJUNG PADA OBJEK WISATA PANTAI TANJUNG PINGGIR DI BATAM - Nurliza; Wibowo, Andri; Lubis, Arina Luthfini (JURNAL MEKAR, 2023)
Batam City, situated within the Riau Islands Province, serves not only as a gateway for international tourists entering Indonesia but also stands as the country's premier tourist destination. Offering a plethora of attractions, including its renowned beaches, Batam City draws both locals and tourists alike seeking leisure and relaxation. Among these, Tanjung Pinggir Beach in Sekupang district holds particular allure. To ensure sustained visitor interest, there is a need to enhance service quality to achieve optimum tourist satisfaction. Employing a qualitative descriptive research approach, data were gathered through various methods such as observation, interviews, documentation, library studies, and questionnaires. The study involved 20 respondents selected through full sampling. Findings revealed that 62% of visitors expressed satisfaction with the attractions, while 69% agreed on the accessibility. However, only 70% reported dissatisfaction with the amenities provided. Consequently, it is imperative for the management of tourist attractions to implement improvements to bolster visitor numbers.